Review Obligations of Real Estate Advertisement Publishers - Xiuji Shan (Studies in Law and Justice, 2023)
Advertisement publishers refers to the media that accept the entrustment of advertisers or advertising operators to publish advertisements to the public, such as television stations, network new media and radio stations. The censorship obligations of advertising publishers means that advertisement publishers actively take reasonable and necessary measures to take the initiative to review the legality of the advertising content and form provided by advertisers or advertising operators. In the current era of digital economy, many real estate enterprises pay too much attention to creating advertising marketing effects, resulting in inducing advertising compliance risks in the content and form of advertising. However, advertisement publishers have insufficient awareness of the importance of advertising compliance, lack of effective violation identification mechanism, lack of spontaneous driving force of advertising compliance system, etc. As a result, the advertisement publishers themselves bear the legal responsibility. This paper will first analyze the legal liabilities that may be caused by the failure to fulfill the obligations of examination from the perspective of advertisement publishers, and then sort out the characteristics of real estate advertising and the main forms of non-compliance of real estate advertising, and finally discuss and propose corresponding compliance strategies.